Protective Effect of Curcuminoids Consumption on Cadmium-Induced Testicular Injury in Albino Rats - Timothy, Amusan A.; Mathias, Emokpae A. (Journal of Pharmacy and Nutrition Sciences, 2024)
This study evaluated the protective effects of curcuminoids against cadmium-induced testicular injury in Albino rats. Male albino rats were divided into nine groups, group 1 (control), groups 2-4 received 120 mg/kg, 240 mg/kg, and 360 mg/kg curcuminoids daily for 28 days without testicular injury. Group 5 received 20 mg/kg cadmium chloride (CdCl2) solution every other day for 28 days (positive control), while group 6 received 20mg/kg CdCl2 + 240 mg/kg curcuminoids every other day for 28 days. Group 7 received 20mg/kg CdCl2 every other day for 28 days, then treated with 240 mg/kg for 14 days. Group 8 received 20 mg/kg CdCl2 solution every other day for 28 days, then treated with 240 mg curcuminoids for 28 days. Group 9 received 20 mg/kg CdCl2 solution every other day for 28 days and left to recover 28 days. Serum and seminal plasma malondialdehyde, catalase, superoxide dismutase, glutathione peroxidase, and glutathione reductase were assayed using Spectrophotometry technique. Semen analysis was determined microscopically. Sperm motility and count were significantly reduced, acrosome defect and percent abnormal sperm morphology were increased among the positive control group when compared with negative control group (p<0.05). Serum GPX, GSH, and SOD, semen GPx , GSH and SOD were significantly reduced (p<0.001), while MDA was significantly increased (p<0.001) in CdCl2 administered rats than negative control. The supplementation of Curcumins resulted in the improvement of sperm quality indices in a dose-dependent manner. Curcumin supplementation may significantly reverse the adverse effects of cadmium chloride testicular injury.